Gas exchange measurements and an indirect estimate of primary production in a holm-oak ecosystem - Manes, F; Vitale, M; Feoli, E; Scimone, M; Canfora, E (FRESENIUS ENVIRONMENTAL BULLETIN, 1998)
An original and simple primary production model is presented. Annual trends of the daily average values of net photosynthesis and leaf transpiration for helm oak are showed. Moreover, primary production data were obtained. To validate the model, an evaluation between estimated results and field measurements was performed, obtaining a strong correspondence.
Citation
Keywords: holm-oak; photosynthesis; plant simulation model; primary production; Transpiration

O3 AND 03+C02 EFFECTS ON A MEDITERRANEAN EVERGREEN BROADLEAF TREE, HOLM OAK (QUERCUS iLEX L.) - Manes, F; Vitale, M; Donato, E; Paoletti, E (Chemosphere, 1998)
The aim of this work is to analyze the effects of a) short-term treatments with different concentrations of 0, (daily 6-hour fumigation with 0, 65, 175 and 300 ppb for 3-4 days); and 6) a medium term treatment with O9 (150 ppb three times a week for thirty days on the whole) and CO2 (700 ppm) on gas exchange, chlorophyll fluorescence, and peroxidase activity in holm oak (Quercus ilex L.) leaves. The results show that net photosynthesis, transpiration, Fv/Frvr ratio and POD activity were not influenced until an O1 concentration of 300 ppb was reached. At this threshold, significant alterations in these physiological and biochemical parameters were found. The treatment with +C02 +O, showed an increase of net photosynthesis suggesting thus an antagonistic effect of CO2 with regard to Oj-induced injuries, while CO2 alone increased photosynthesis and decreased transpiration but induced no effects on FV/‘F, ratio or peroxidase activity. From our data, holm oak shows a resistance to episodes ofphotochemical 0, stress, that in the Mediterranean region can reach peaks of > 100 ppb. This response is likely to be due to the morpho-anatomic structure of helm oak leaves and their sclerophyllous adaptations. This might leads helm oak to adopt a stress tolerance strategy with regard to leaf response to O,, the effects of which cannot be ameliorated by an increase of atmospheric CO2
Keywords: CO2 (voyant); Holm oak; Net photosynthesis; ozone exposure; peroxidase activity; Transpiration